Assessment of the risk factors for periodontitis in patients attending the Hospital Universiti Sains Malaysia: a retrospective study - Arshad, Sohaib (2023)
Periodontitis is a severe form of gingival disease characterized by infection and inflammation of the bone and connective tissue supporting the teeth. According to the Global Burden of Disease study, periodontal disease was the 11th most prevalent condition globally. The incidence and prevalence of periodontitis can be influenced by various factors, including age, gender, genetics, smoking, systemic health disorders (such as diabetes), low socioeconomic status, and practices related to oral hygiene. Two hundred seventy-four subjects were included. This was a retrospective study and subjects includes periodontitis patients who attended School of dental sciences ar Universiti Sains Malaysia between the year 2011 to 2020.The patient's name, age, sex, ethnicity, education, address, and income were retrieved from the patients record. Additionally, main presenting complaints, dental examination record, history of systemic diseases, allergies, medication history, prior dental operations, severity and diagnosis of periodontal disease, and list of past dental procedures were all documented. Further, the DMFT, Plaque index, Gingivitis score and pocket depth were recorded. The data was transferred to the Excel sheet and then processed and analysed using SPSS. A total of 274 subjects (male: 51.8% and female: 48.2%) participated in this study. The median age was 51.0 years. Most subjects were Malay (92.3%) and employed (70.8%). Furthermore, most subjects had no habits (71.2%) or no allergic reactions (84.7%). For the medical characteristics, more than half (57.9%) of the subjects had no other medical condition, with the prevalence of hypertension and diabetes at 31.8% and 15.0%, respectively. The study found that gingivitis score had a significant and negative correlation with subjects’ percentage pocket depth < 4mm (r = -0.13, p = 0.038) and a significant and positive correlation with percentage pocket depth 4-6mm (r = 0.15, p = 0.032). The results of the logistic regression analysis show that two factors (i.e., age group and ethnicity) were retained in the final model and therefore considered significant predictors of periodontitis (≥4mm). For age group, the 18–44-year-olds were 2.7 times more likely to have periodontitis than the 65-year-olds and above (AOR = 2.73, p = 0.066), and the 45–64-year-olds were 3.0 times more likely to have severe periodontitis than the 65-year-olds and above (AOR = 3.04, p = 0.035). For ethnicity, the Malays were 12.5 times more likely to have periodontitis than the others (AOR = 12.50, p = 0.015). Ethnicity was the only sociodemographic factor that had a statistically significant association with the severity of periodontitis. The gingivitis score was the only clinical parameter significantly associated with the periodontitis severity (p=0.01). Significant predictors of periodontitis were the sociodemographic factors such as age group and ethnicity determined by binary logistic regression analysis